“Here’s looking at you, kid:” an empirical study of the social movie quoting phenomenon - Smyers, John Otis (Kansas State University, 2016)
To date, no research has been conducted to establish the discourse goals accomplished through social movie quoting. In this thesis four studies were conducted to learn what discourse goals are accomplished through social movie quoting and if Roberts and Kreuz’ (1994) discourse goal taxonomy for figurative language would be a suitable theoretical framework for the study of the social movie quoting phenomenon. Study 1 examined movie quoting without being tied to any specific movie quotes. Demographic variables were correlated with common movie viewing preferences, behaviors, and attitudinal responses. Study 2 had participants generate a realistic movie quote they would actually use for accomplishing each of several specific discourse goals in conversation. Study 3 had participants generate a plain English interpretation of the movie quotes selected from Study 2. Study 4 participants rated the movie quotes and plain English equivalents generated in studies 2 and 3 for aptness and likelihood for use in conversation with the knowledge (Condition 1) and without the knowledge (Condition 2) of the underlying discourse goal. Quotes were randomized and counterbalanced so that half the participants in each condition received all movie quotes first (Group 1) and half the plain English first (Group 2). Results indicated that movie quotes were used to accomplish a set of discourse goals most similar to the traditional figures of speech of hyperbole, understatement, metaphor, and simile. The most common purposes of social movie quoting were to compare similarities and either downplay or exaggerate these similarities. Knowledge of the underlying discourse goal significantly increased the aptness and likelihood of both quote types for several discourse goals. The order of presentation did not significantly affect participants’ ratings. The aptness of the quote was strongly related to participants’ likelihood of using a particular quote, regardless of quote type. Future research should focus on capturing naturally occurring language to further increase the ecological validity of these results. It appears that the act of quoting movie lines in conversation is heavily dependent on individual preferences and a method should be developed to capture movie quoting in such a way. Suggestions for enhanced selection of movie quotes is discussed.
Keywords: figurative language; movie quoting; discourse goals